Pandemi Covid-19 dan Inovasi Perpustakaan Perguruan Tinggi - Deri Hediana Priyadi; Sukaesih Sukaesih; Evi Nursanti Rukmana; Samson CMS (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2020)
The Covid-19 pandemic has had a huge impact on all elements of society, including information institutions such as libraries. Innovations made by information institutions such as libraries are mostly carried out on the development of library collections, library services, human resources. The purpose of this research is to look at innovations in college libraries in providing services to academicians due to covid-19. Digital libraries exist as an innovation in overcoming the problems of the Covid-19 pandemic. The research method uses descriptive qualitative methods, researchers conducted online interviews by sending emails to the email library. The data were obtained by interviewing the librarian of the college library. Innovations made in libraries involve human resources, library collections, and services. Increasing human resources in the library by providing training on deficiencies in terms of services, turnover of librarians aims to provide officers with new experiences. Library collections experience sharing of resources where collaboration between libraries aims to fill the void in library collections in the library. Internship in libraries can be a movement in terms of library development, where the internship is a place to accommodate young people who are rich in creative ideas and incoming invoices that make libraries more colorful.